The Exercise Model of Shooting Skills for the Beginner Players Women's of Futsal - Ahmad Rizal; Hernawan Hernawan; Iman Sulaiman (BIRCU, 2019)
The aim of this study is to develop a shooting skill exercise model design for beginner players women's of futsal to obtain empirical data about the effectiveness of the results of shooting skill exercise models for beginner players women's of futsal. The method used in this study is the research and development method of Borg and Gall which consists of ten steps. The subject of this research is a beginner woman futsal player. The final results of this study are model manuals and shooting skills exercise video models for woman futsal players with a final model number of 27 models that have gone through expert evaluation, trial and revision, and effectiveness has been tested. The effectiveness of the application of shooting skills exercise models for woman futsal beginners uses the